The influence of aging on spinal motoneuron excitability in healthy subjects - Ohkuma, Aya; Komori, Tetsuo; Kitao, Ruriko; Abe, Tatsuya; Hirashima, Fumiko; Kimura, Toshinori (Japanese Journal of Clinical Neurophysiology, 2020)
This study aimed to assess the relationship between the physiological loss of motor units and spinal excitability in aging process of healthy person. Multiple point stimulation technique was used to calculate MUNE and 100 F-wave were analyzed to determine the spinal excitability by F-wave persistence (FP) and the amplitude ratio between F-wave and CMAP (F%M) at right median nerve of sixty-four healthy volunteers (mean age, 43.1 years). We divided the subjects into four groups, young adult (18 to 30 years), adulthood (31 to 45 years), middle-aged (46 to 59 years), and older group (above 60 years). MUNE decreased in elder group compared with young and middle age groups. Whereas, FP and F%M increased in high-middle and elder groups compared with young group. Multiple regression analysis showed significant relation between the MUNE decrease with FP increase and aging. We concluded the aging process, which was known as motor neuron loss, was compensated with excessive spinal motoneuron excitability which was the result of dysregulation of inhibitory process from central nervous system.